The Role of Personality, Family Environment and Entrepreneurship Education on Entrepreneurial Interest of Batam State Polytechnic Students During the Covid-19 Pandemic - Salwa Anisa; Adi Irawan Setiyanto (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2022)
The purpose of this study was to determine the influence of personality, family environment, and entrepreneurship education on the entrepreneurial interest of Batam State Polytechnic students during the covid-19 pandemic. The research population is Batam State Polytechnic students with the criteria that they have received entrepreneurship course. The total respondents were 381 students. This study uses a quantitative approach and data collection through distributing questionnaires using google form. The results of the study are personality variables have an effect on student entrepreneurship interest. The family environment variable has no effect on the student's entrepreneurial interest. Finally, the entrepreneurship education variable has an effect on students' interest in entrepreneurship. The implications of the research are for Polibatam students to take part in entrepreneurial training and hone skills that can motivate themselves to become entrepreneurs. The implication for Polibatam is to become a facilitator and support activities that can increase students' interest in entrepreneurship.